A la mesa con Magallanes, Elcano y Pigafetta. - AGUILAR DOMINGO, MARÍA SOLEDAD; PÉREZ VÁZQUEZ, MARÍA ENRIQUETA (Scripta)
This article is dedicated to the analysis of the difficulties of interpretation, and therefore of translation, represented by the terms related to food in the Relazione del primo viaggio attorno al mondo, a work in which Antonio Pigafetta narrates the first circumnavigation of the globe. The first part of the study describes the manuscript that narrates the first circumnavigation of the globe and its objectives. The second part examines the terms, locutions, etc. of the food in the Relación, and the third part analyses the difficulties and translation problems caused by some of the terms related both to the food supplied in the initial provisioning of the ships and to the exotic foods of the places where the ships made landfall during the almost three years that the expedition lasted. Our translation (in press) and the translatological study presented here is based on the annotated edition produced by Andrea Canova in 1999. The numbers preceding each paragraph also belong to the edition of that text.